Solidarność . biuletyn informacyjny PRK-9, no. 4, 1981 - [Sekcja Informacyjno-Programowa NSZZ "Solidarność" przy PRK-9, ed. Jan Pacula, Jacek Swałtek, Maria Lorek] (NSZZ "Solidarność" PRK-9, 1981)
Creation and circulation: For workplace internal use